The Expansions of Vehicle Routing Problems: A Logistical Overview - Saragih, N. I. (International Journal of Psychosocial Rehabilitation, 2020)
This paper provides an overview of the expansions of VRP (vehicle routing problems) from a logistical point of view. The expansion includes the integration between VRP and inventory problems. That integration is known as IRP (inventory-routing problems). Another expansion is the integration of VRP with location problems, which is then known as LRP (location-routing problems). The last expansion is known as LIRP (location-inventory routing problems), which is the integration between VRP, inventory problems, and location problems. This paper also provides suggestions for future research related to the expansion of VRP.